2017
DOI: 10.1002/14651858.cd011986.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Complete versus culprit-only revascularisation in ST elevation myocardial infarction with multi-vessel disease

Abstract: Compared with culprit-only intervention, the complete revascularisation strategy may be superior due to lower proportions of long-term cardiovascular mortality, long-term revascularisation, and long-term non-fatal myocardial infarction, but these findings are based on evidence of very low quality. TSA also supports the need for more RCTs in order to draw stronger conclusions regarding the effects of complete revascularisation on long-term all-cause mortality, long-term cardiovascular mortality, and long-term n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Another weakness of this meta-analysis is that although the included trials were performed in different parts of the world, some continents were underrepresented 4. For instance, none of the included trials studied patients in North America, South America or Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Another weakness of this meta-analysis is that although the included trials were performed in different parts of the world, some continents were underrepresented 4. For instance, none of the included trials studied patients in North America, South America or Australia.…”
Section: Discussionmentioning
confidence: 99%
“…refractory angina, proven ischaemia, and repeat revascularization) in the composite endpoints [2,3,6]. A meta-analysis that focused on all-cause and cardiovascular death found that CR may be better than IR [16], but the quality of evidence on which this was based was poor and the COMPLETE and COMPARE ACUTE trials were not included [4,5]. COMPLETE is the largest prospective study conducted to date and showed that CR is better than IR for the composite outcome of cardiovascular death or myocardial infarction (HR 0.74, 95% CI 0.60−0.91; p = 0.004), driven primarily by a reduction in myocardial infarction [4].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, significant narrowings are observed in several vessels and the physician needs to decide whether to treat all the narrowings or focus on the most a↵ected coronary artery. Several randomized trials and meta-analyses found that complete revascularization, where multiple narrowed arteries are treated, was associated with lower mortality in STEMI patients with multivessel disease compared to single-artery treatment (Bravo et al, 2017). For patients with multi-vessel disease, a larger number of segments treated and stents inserted may therefore reflect a "better" treatment.…”
Section: Datamentioning
confidence: 99%